(untitled) (Journal of Eye Movement Research, 2011)
The current study investigated how a post-lexical complexity manipulation followed by a lexical complexity manipulation affects eye movements during reading. Both manipulations caused disruption in all measures on the manipulated words, but the patterns of spillover differed. Critically, the effects of the two kinds of manipulations did not interact, and there was no evidence that post-lexical processing difficulty delayed lexical processing on the next word (c.f. Henderson & Ferreira, 1990). This suggests that post-lexical processing of one word and lexical processing of the next can proceed independently and likely in parallel. This finding is consistent with the assumptions of the E-Z Reader model of eye movement control in reading (Reichle, Warren, & McConnell, 2009).